(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the Soviet government’s policies of "Military Communism," "New Economic Policy," and their consequences as the first emergency economic measures. This refers to the Bolsheviks’ economic policy aimed at administrative-command management, including "Food Deployment," the elimination of private property, a planned economy, and the pursuit of quantity.